Acarbose, a Pseudooligosaccharide, Is Transported but Not Metabolized by the Maltose-Maltodextrin System of Escherichia coli - Brunkhorst, Claudia (American Society for Microbiology, 1999)
The pseudooligosaccharide acarbose is a potent inhibitor of amylases, glucosidases, and cyclodextrin glycosyltransferase and is clinically used for the treatment of so-called type II or insulin-independent diabetes. The compound consists of an unsaturated aminocyclitol, a deoxyhexose, and a maltose. The unsaturated aminocyclitol moiety (also called valienamine) is primarily responsible for the inhibition of glucosidases. Due to its structural similarity to maltotetraose, we have investigated whether acarbose is recognized as a substrate by the maltose/maltodextrin system of Escherichia coli. Acarbose at millimolar concentrations specifically affected the growth of E. coli K-12 on maltose as the sole source of carbon and energy. Uptake of radiolabeled maltose was competitively inhibited by acarbose, with a K(i) of 1.1 μM. Maltose-grown cells transported radiolabeled acarbose, indicating that the compound is recognized as a substrate. Studying the interaction of acarbose with purified maltoporin in black lipid membranes revealed that the kinetics of acarbose binding to LamB is asymmetric. The on-rate of acarbose is approximately 30 times lower when the molecule enters the pore from the extracellular side than when it enters from the periplasmic side. Acarbose could not be utilized as a carbon source since the compound alone was not a substrate of amylomaltase (MalQ) and was only poorly attacked by maltodextrin glucosidase (MalZ).